Enterprise risk management in today's world : a current and futuristic view of the complexity, resilience, responsibility and tools in ERM - Louisot, Jean-Paul (Emerald studies in finance, insurance, and risk management, 2024)
In recent years events such as a global pandemic, huge technological changes, and war in Europe have demonstrated how organizations manage risk is more important than ever. Plans, models and ideas to mitigate disruptive situations are needed to ensure future success. Enterprise Risk Management in Today's World examines enterprise risk management in its past, present and future, exploring the role that directors and leaders in organizations have in devising risk management strategies, analysing values such as trust, resilience, CSR and governance within organizations. Benefiting students, researchers and high-level decision makers, this volume fills a gap in the existing literature of the interaction between business and society in the field of enterprise risk management. Emerald Studies in Finance, Insurance, and Risk Management provides a platform for authors to explore, analyse and discuss current and new financial models and theories, and engage with innovative research on an international scale. Subjects of interest may include banking, accounting, auditing, compliance, sustainability, behaviour, management, and business economics.